Rapid growth of selected Asian economies : lessons and implications for agriculture and food security - FAO Regional Office for Asia and the Pacific; Food and Agriculture Organization of the United Nations (Bangkok : Regional Office for Asia and the Pacific, Food and Agriculture Organization of the United Nations, 2006)
Discusses experiences in agricultural development and economic growth and the implications of rapid growth; provides insights on agricultural restructuring in response to changing market and trade opportunities. The intended audience is governments, policy professionals and development practitioners in crafting national policies and strategies for rapid and sustained agricultural growth to achieve the Millennium Development Goals of poverty and hunger eradication
Keywords: Rural development; Food supply; Agriculture and state; Economic development